Low-power TCAM for regular expression matching - Lin-xuan DING; Kun HUANG; Da-fang ZHANG (Tongxin xuebao)
A character-indexed regular expression matching algorithm was presented to address the limitations of TCAM power consumption. This algorithm used the idea of separating the alphabet table from the states in deterministic finite automaton (DFA) for building a character index, in order to reduce the number of activated TCAM blocks, which in turn translated low TCAM power. Experimental results showed that proposed algorithm reduces the TCAM power by 92.7% on average as well as the TCAM space usage by 32.0% on average, and improves the matching throughput by 57.9% on average compared to previous solutions based on DFA.